Turn It Up and Open the Window: On the Rebound Effects in Residential Heating - Hediger, Cécile; Farsi, Mehdi; Weber, Sylvain (My University, 2018)
This paper investigates how households respond to efficiency improvements of their heating system. The analysis is based on the stated preference approach with an innovative choice experiment. The design includes questions to quantify both the direct and indirect rebounds. A series of easy discrete possible changes have been suggested to prime the respondents for deciding on potential actions impacting their heating service demand. Responses to these qualitative choices are moreover used to cross-validate the quantitative results. Overall, we find relatively low direct rebound effects. However, after accounting for the indirect rebound calculated using energy embodied in goods and services purchased by re-spending initial savings, we estimate an average total rebound of about one third. The econometric analysis points to substantial variations across individuals that are partly explained by observed characteristics. The results are consistent with the conjunction that heating is a basic need which calls for little rebound in high-income groups.
Keywords: Rebound effects; Energy efficiency; Residential heating; Double hurdle model; Stated preferences; Contingent behaviour model; Online experiment.